Pengaruh Worklife Balance, Reward dan Disiplin Kerja terhadap Kinerja Pegawai pada Balai Diklat Keagamaan Padang - Elva Dona; Mutya Novar Minda (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Employee performance will increase if employees feel satisfied in their work. To grow employee job satisfaction, companies must be able to respond to employee needs such as psychological needs, namely work-life balance and material needs which are also very important for employees, namely reward policies, the key to creating an orderly and productive work environment, namely work discipline. The purpose of this study was to determine the influence of work-life balance, rewards and work discipline on employee performance at the Padang Religious Training Center. Through the questionnaire method with samples using purposive sampling techniques, there were 71 respondents who were used as samples in this study. In the hypothesis testing that has been carried out, it can be concluded that work-life balance has a positive and significant effect on employee performance at the Padang Religious Training Center, rewards have a positive and significant effect on employee performance at the Padang Religious Training Center and work discipline has a positive and significant effect on employee performance at the Padang Religious Training Center.